Development of Riverside Areas in the Context of the Attractiveness for Residents - Klimek, Mateusz; Bosowski, Wiktor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to analyze the tourism potential in the riverside areas of selected cities in Lubuskie Voivodeship located in the Oder River valleys. The research issue of the article was defined as a way to measure tourist potential in the development of riverside areas. In the research phase, based on the comparative multi-criteria method, special attention was paid to the accessibility of the river for the inhabitants, their usefulness for the recreation, as well as the location of the recreational infrastructures in the river valleys.
Keywords: riverside areas; tourist potential; river potential; development of riverside areas; attractiveness for residents; Oder River valley; lubuskie voivodeship; tereny nadrzeczne; potencjał turystyczny; potencjał rzeki; zagospodarowanie terenów nadrzecznych; atrakcyjność dla mieszkańców; Dolina Odry; lubuskie